Redes de cooperação : uma análise do perfil econômico regional nos assentamentos do município de Cláudia localizado na Amazônia Mato-grossense - Gireli, Bárbara Tairine Campos (2021)
Small Brazilian farmers constantly suffer a series of contingencies, such facts make them have difficulties in accessing technological packages, production flow, among others. In this sense, cooperation networks have a unique role for them, as by organizing themselves in these structures, they can reduce transaction costs, thus increasing their competitiveness. Thus, this study carried out an analysis of the cooperation networks of the municipality of Cláudia, which is a peripheral city located in the Amazon biome, thus investigating the main characteristics of the families included there, both those that are part of a network and those that are part of a network. which are not. parts of the networks as a way to build a counterfactual, thus seeking to understand if the cooperation networks installed in the settlements were fostered and trained by institutions that work with family farming. The research used the mixed method for greater understanding, thus using bibliographical, documental and field research. In the field research, a semi-structured questionnaire was used, applied to families located in the Keno and Terra de Viver settlements. Questionnaires were also applied in institutions that serve these families. The main results show that 51.52% of respondents are part of a bureaucratic cooperation network and 62.87% are part of a social network, it was possible to identify networks between institutions, families, cooperatives and associations. Through the questionnaire data, four indexes were also developed, namely: quality of life; human and endogenous; institutional; and social index. When we compare the difference of means in such indices, we cannot find a significant difference, except in the human and endogenous development index. From this fact, the Propensity Score Matching method was applied, to understand if when comparing the two groups where their members have similar conditions, we would still have differences. Thus, it was possible to verify that the farmers who are part of the cooperation network have a higher level of human and endogenous capital being 62.1. This act highlighted the importance of cooperation networks forsmall producers, since those who are part have a higher level of human and endogenous capital, which is fundamental for local and regional development, as it performs interactions between agents, thus increasing their competitiveness and capacity for development.